Taekwondo basics : everything you need to get started in taekwondo - from basic kicks to training and competition - Shaw, Scott, 1958- (Tuttle Publishing, 2018)
Are you planning to learn Taekwondo, but don't know where to begin? Are you looking for a teacher? Are you taking a class but confused by the technical terms used for the kicks and moves? Taekwondo Basics teaches you all the fundamentals of this martial art form in a clear and easy-to-understand manner! This essential reference contains the following vital information: The origins of Taekwondo-its philosophy, history, and different skills How to find a teacher and a class that are right for you Getting ready for your first class-what happens in a Taekwondo class? The essential elements-stances, blocks, hand and arm strikes and kicks How to complement your Taekwondo training with other conditioning exercises, such as running and biking Powerful ways to improve your technique through target training, partner training, competitive training, free-sparring, and more Resources that can help you further develop your Taekwondo trainingWhether you're just getting started, or you've already been training for a year or two, Taekwondo Basics offers an easy to read, and yet comprehensive introduction to the sport.